Sustainability of Agricultural Cooperative Societies in Nigeria: The Case of South-South Zone, Nigeria - Ndifon, H. M.; Agube, E. I.; Odok, G. N. (Richtmann Publishing, 2012)
The study looked at the sustainability of agricultural cooperative societies in the south-south geopolitical zone ofNigeria. Out of six states of the zone, Cross River, Rivers and Edo were randomly selected for the study. The study identified thesocio-economic characteristics of cooperative societies, analyzed loan advanced to cooperative members, focus on the scopefor sustainability of cooperative societies, women empowerment and analyzed the loan utilization by the cooperative members.Secondary data was sourced from the Nigerian Agricultural Cooperative and Rural Development Bank (NACRDB), CalabarBranch. The information was analyzed using descriptive statistics. The result showed that out of the total loan advances made,more than 50% went for consumption purposes. Rough estimate shows that about 50% of the cooperative members fall belowpoverty line which shows that the cooperative groups of the zone comprised mostly of the economically poor.